ESTIMATIVA DE VIDA ÚTIL DO PBX (plastic-bonded explosive) COM ENVELHECIMENTO ACELERADO - Kirchhof,Edemar (2016)
This article aims to estimate the shelf life of the PBX by thermal analysis estimated by the Arrhenius equation, equivalent to the time of storage at accelerated aging. The PBX was subjected to accelerated aging in an oven at controlled temperature 60 ºC for periods of 5, 10, 15 and 25 weeks, which are equivalent to 5, 10, 15 and 25 of natural aging, respectively, at a temperature of 25 ºC. The curves of thermal decomposition of the samples were obtained by the DSC (Differential Scanning Calorimetry) technique. The kinetic parameters, such as the activation energy and pre-exponential factor, were determined by the Ozawa method and the Kissinger method. Initial results of this study indicated that, for a period of 25 years of storage in the cargo hold, the material did not change this aging significantly. To study the life of PBX analyzes, vacuum chemical stability were also conducted to verify the safety of explosive handling.